Overview of the laboratory tests for geoenvironmental characterisation of construction and demolition waste - Carmona Wilches, Johana Marcela [UNESP]; Rodrigues, Roger Augusto [UNESP]; Mondelli, Giulliana [UNESP] (Springer Nature, 2025)
This paper presents a comprehensive database on the morphological, mineralogical, chemical, and contaminant release characteristics of construction and demolition waste (CDW). Scanning Electron Microscopy (SEM) was employed to analyse the particle morphology, revealing their angular and porous nature. X-ray Diffraction (XRD) was used to identify key minerals, such as quartz, calcite, and gypsum, providing vital information on the mineralogical composition of CDW. X-ray Fluorescence (XRF) analysis allowed the characterisation of the elemental composition, highlighting predominant oxides, like SiO₂, Al₂O₃, and CaO, with a notable presence of Na₂O in glass waste. Critical oxides, such as Fe₂O₃ (8.78%) and MgO (14.19%), were also identified. Recycled aggregates exhibited higher porosity and water absorption compared to natural aggregates, with fines constituting less than 27%, which presents an opportunity for their reuse, particularly in the production of geopolymers. Organic matter content was low, reaching up to 4.6%. The main contaminants identified include arsenic, cadmium, lead, chromium, and sulphates, with sulphate concentrations reaching up to 6,000 mg/kg, while arsenic, chromium, and lead reach up to 28 mg/kg, 310 mg/kg, and 6,580 mg/kg, respectively. These findings support the adoption of circular economy principles and regulatory frameworks that promote recycling and the use of innovative materials, thereby reducing the environmental footprint of construction projects.
Keywords: CDW reuse; Circular economy; Construction waste; Recycling; Waste characterisation; Waste valorisation